MAKSIMALISASI PENATAAN RUANG KELAS DALAM MEMBENTUK LINGKUNGAN BELAJAR PENDIDIKAN AGAMA ISLAM YANG INTERAKTIF DAN INOVATIF - Pane, Astriana Sitorus; Afandi, Muslim; Subhan, Muhammad (JURNAL KAJIAN ISLAM MODERN, 2025)
Classroom spatial arrangement plays a pivotal role in enhancing the effectiveness of Islamic Religious Education (PAI), particularly in fostering an interactive and innovative learning atmosphere. This study synthesizes principles of space management, ergonomics, and digital technology integration, combined with Islamic aesthetic values and a constructivist learning approach, to design classrooms that actively engage students. Adopting a qualitative methodology, the study draws on literature from various sources concerning classroom design and PAI pedagogical practices. Findings indicate that spatial configurations mindful of seating height, movement flow, and accessibility significantly facilitate interaction between teachers and students, as well as among students themselves. Furthermore, flexible layouts such as clustered seats, U-shaped formations, and designated activity zones strongly support collaboration and the internalization of religious values.